Criopreservação de sêmen equino em diluidores contendo os antioxidantes lactoferrina e catalase. - Hariany Seabra Martins (2015)
The objective of this study was to improve frozen sperm quality with the addition of lactoferrin (Lf) and catalase (Cat) to an equine semen freezing extender and evaluate the in vitro fertilizing ability. Semen was frozen with the extenders: C1) Control INRA 82, C2) C1 + 500μg/mL Lf, and C3) C1 + 200 IU/mL Cat. Sperm motility characteristics, membrane integrity and functionality, spontaneous acrosome reaction, iron and reactive oxygen species concentrations were evaluated. To estimate the in vitro fertilizing ability, the sperm were submitted to the capacitation and hyperactivation (H2 and H3) protocols: H1) Control: modified Whitten’s capacitation medium, H2) H1+Procaine 5mM, H3) H1+Calcium Ionophore A23187 5μM (CaI). Sperm motility (CASA), acrosome reaction and membrane integrity rates were analysed and bovine sperm zona pellucida (ZP) binding assay performed. The iron concentration was lower and membrane functionality was higher in the Lf treated sperm compared to the control group (P<0.05). The number of bovine ZP sperm binded did not differ between the capacitated with Whitten’s medium and Procaine hiperactivated sperm, however, it was lower in the CaI hiperactivated group. It was concluded that the addition of Lf was beneficial to the frozen equine semen quality while CaI was detrimental to the ZP sperm binding.